Importance of Business Intelligence tools for the analysis of indicators acreditation - Acuña Caicedo, Roberto W.; R. Caicedo, Christian; Rodríguez González, Antonieta (Revista Universidad de Guayaquil, 2015)
This research is focused on the importance of using the tools of busines intelligence. For the analysis of the indicators of accrediting, terminal efficiency, retention rate, and nivelation of the generic model for the assessment of the presence and semi presence careers in Ecuador. For accomplishing this, it was estat blished to perform an analysis of the data base of computational sciences and networking engineer career. The investigation was carried out in computational sciences and networking engineer career of the South of Manabi State University. In this Project, it was established as a main objective to know the importance of using the tools of Business Intelligence Pentaho y RKward for the generation of new information. All of this as a strategy for designing the indicators of accrediting. For the development of this memory, it was used as a metodology some instruments based on documents, analysis techniques of data bases, observation forms, surveys, and interviews applied to students and teachers. As a conclusión, this research helps to get new information to develop indicators for credditing by using Bl, Pentaho y RKward